Discovery of interspecific alloparental care of silver‐eared mesia nestlings by a mountain bulbul - Jianping Liu; Bin Li; Wei Liang (Ecology and Evolution)
Abstract Although brood parasitism has been well documented among bird species, interspecific alloparenting, which is parenting behavior of adult individuals of one species toward the progeny of another species, is increasingly being reported. However, compared with the many reports of interspecific alloparenting behavior in North America and Europe, this phenomenon is less well known in China, with only two prior cases of interspecific alloparenting behavior in birds having been recorded. On June 23, 2022, we observed an instance of interspecific alloparental care provided by a mountain bulbul (Ixos mcclellandii) towards silver‐eared mesia (Leiothrix argentauris) nestlings in Caihu Village, Jingdong County, Yunnan Province, southwestern China. We recorded 19.5 h of footage during the period in which the mountain bulbul provided care for the nestlings with the aim of documenting detailed observations of interspecific alloparenting to contribute to our overall understanding of this behavior. The alloparenting behavior of the mountain bulbul lasted for at least 5 days. During this period, both silver‐eared mesia parents fed their nestlings 157 times and removed their nestlings' fecal sacs 5 times, while the mountain bulbul fed the nestlings 30 times and removed the nestlings' fecal sacs 4 times. In addition, the male silver‐eared mesia parent chased the mountain bulbul away during nestling feeding. As there was no life history information for the mountain bulbul at that time, we were unable to directly determine why it exhibited interspecific alloparental care. Regardless of the reason for the mountain bulbul's behavior, these findings provide valuable information for future studies on the reproductive ecology of these two bird species.